How to manage emergency response of health teams to natural disasters in Iran: A systematic review - Hamid Reza Mehryar; Omid Garkaz; Mojtaba Sepandi; Maryam Taghdir; Sahar Paryab (Archives of Trauma Research, 2021)
Background and Objectives: Disaster as a natural devastating event leads to terrific injuries, morbidities, and mortalities, particularly in developing countries. The aim of this study was to evaluate the management of emergency response of health teams to natural disasters in Iran. Materials and Methods: Some international databases, such as PubMed, ISI, and Scopus, were searched to find English articles between May 2000 and May 2019. Finally, 22 published articles were entered into the study. Keywords included “disaster,” “flood,” “earthquake,” “wildfires,” “tornadoes,” “hurricanes,” “drought,” “famine,” “natural catastrophe,” “storms,” “avalanche,” “health team,” and “Iran” or a combination of them in the title/abstracts. Results: There were >12618 relevant research articles; in this systematic review, 22 published articles consisted of two interventional, one modeling, nine qualitative and ten cross-sectional studies were included. We used Strengthening the Reporting of Observational Studies in Epidemiology Checklist, a checklist of items that should be included in reports of observational studies for selected articles. The summary of the selected articles the selection process using Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Conclusions: The findings of the current study revealed that two subjects were important; extra education in the college course and in-service training at hospitals using educational pamphlets and having a special committee to manage the disaster.